Oscillations of Skin Microvascular Blood Flow in Patients with Asthma. (January 2016) - Tikhonova, Irina V.; Kosyakova, Ninel I.; Tankanag, Arina V.; Chemeris, Nikolai K.
Abstract: Objective: This research is aimed at studying the features of skin blood flow oscillations in patients with severe persistent atopic BA during a period of fine control over symptoms. Methods: The study of microcirculation was carried out by LDF at rest and in response to a transient ischemia in 20 patients. The time‐amplitude adaptive wavelet analysis of the blood flow oscillations was conducted to elucidate the peculiarities of microcirculatory regulation system functioning. Results: No significant changes were revealed for SBP and the oscillation amplitudes in the cardiac (0.6–2 Hz) and respiratory (0.145–0.6 Hz) intervals, both at rest and in response to transient ischemia, in patients compared to the control group. A consistent twofold decrease in the oscillation amplitudes was found in the neurogenic (0.021–0.052 Hz) interval at rest, as well as in the myogenic (0.052–0.145 Hz) and NO‐dependent endothelial (0.0095–0.021 Hz) intervals both at rest and during the postocclusive reactive hyperemia in patients with lung obstruction (FEV1 < 80%) in comparison with a control group. Conclusions: The amplitudes of skin blood flow oscillations in the myogenic, neurogenic and NO‐dependent endothelial intervals in patients with obstruction are different from those in patients without obstruction.